The Dynamics of Party System in India: A Comparative Study of National and Regional Parties - Bharti, Mukesh Shankar (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2022)
The purpose of the study is the structure of political parties and comparative analysis of the party system in the Republic of India. The objective of the research is to investigate the functioning of the parties, power structure, dynamics and their role in forming the government at the centre and state levels in the country. In addition, the study analyses the approaches of the parties as an actor to make a coalition government in various provincial governments. The research used comparative method analysis to achieve the purpose of this study and describe the source methods for testing the research objectives. The study finds the comprehensive relevance of parties’ role in the Indian political system. Finally, the result of the article finds as a conclusion that the multi-party system provides multiple opportunities for people to participate in the democratic process in India.

Celem opracowania jest struktura partii politycznych oraz analiza porównawcza systemu partyjnego w Republice Indii. Celem pracy jest zbadanie funkcjonowania partii, struktury władzy, dynamiki oraz ich roli w tworzeniu rządu na szczeblu centralnym i stanowym w kraju. Ponadto w opracowaniu przeanalizowano podejście partii jako podmiotu tworzącego rząd koalicyjny w różnych rządach prowincjonalnych. W badaniu zastosowano analizę metodą porównawczą, aby osiągnąć cel niniejszego opracowania, oraz opisano metody źródłowe służące sprawdzeniu celów badawczych. Badanie wykazało wszechstronne znaczenie roli partii w indyjskim systemie politycznym. Wreszcie, w wyniku artykułu stwierdzono, że system wielopartyjny zapewnia ludziom wiele możliwości uczestniczenia w procesie demokratycznym w Indiach.
Dynamika systemu partyjnego w Indiach: Studium porównawcze partii narodowych i regionalnych
Keywords: Party System; National and Regional Parties; Democracy; India; Government; system partyjny; partie narodowe i regionalne; demokracja; Indie; rząd